MODEL OF THE INTELLECTUAL SUBSYSTEM OF KNOWLEDGE CONTROL WITH MULTI-LEVEL ADAPTIVE TESTING - Кравченко, Ольга Віталіївна; Плакасова, Жаннетта Миколаївна (Eastern-European Journal of Enterprise Technologies, 2010)
The analysis of existing adaptive systems of training is made. The structure of the intellectual (adaptive) monitoring system of knowledge which has in structure the supervising unit with the analysis of training results (АTR) is offered.